Taxonomy and nomenclature of Enicocephalus flavicollis Westwood—type species of the type genus of the Enicocephalidae (Hemiptera: Heteroptera: Enicocephalomorpha) - Štys, Pavel; Baňař, Petr (Zootaxa, 2012)
The status and location of the type series of Enicocephalus flavicollis Westwood, 1837 (type species of EnicocephalusWestwood, 1837, the type genus of Enicocephalidae) from St. Vincent Island (Lesser Antilles) is discussed, and insteadof two formerly assumed different ‘holotypes’ the lectotype and paralectotype are designated. Males of E. flavicollis areredescribed, the 5th instar larva is described for the first time, and diagnostic characters of the species are reviewed. Spe-cies of Enicocephalus are listed and pterygopolymorphism of females is reviewed. Enicocephalus dominica Bruner, 1924 is a correct original spelling of the species name (not E. dominicus nor E. dominicanus).